Análise da utilização do Instagram como uma ferramenta viável de empreendedorismo: um estudo de caso com empresas potiguares - Silva, Dhiego Abnner de Medeiros (Universidade Federal Rural do Semi-Árido, 2019)
With the current scenario of unemployment and low capital in the country, many unemployed people see entrepreneurship as a way to earn money and among the many ways to undertake digital marketing has been growing in the country and the world. Thus, this work aims to analyze the importance of Instagram, one of the most used social networks in the world in the entrepreneurial environment. Instagram has been offering itself as a great tool to create your business and generate income without major costs. The research method employed consisted of the application of a depth questionnaire in two companies that have commercial profiles in Instagram. The results point to the importance of this tool for entrepreneurship, because it presents several benefits, such as ease of interaction and low cost. The work is mainly justified in two ways: the first is the current theme and the second is the increasing volume of business that has been carried out by the Internet.
Artigo Acadêmico
Keywords: Instagram; Redes sociais; Empreendedorismo; Instagram; Social networks; Entrepreneurship; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA